Impact of Medical Comorbidities on Ketamine and Esketamine Treatment Effectiveness for Posttraumatic Stress Disorder and Depression: A Clinical Outcomes Analysis from the VA San Diego Healthcare System - Zhang, Sijia; Afshar, Houtan; Colvonen, Peter J.; Nokes, Brandon; Compton, Jason; Mishra, Jyoti; Bismark, Andrew W.; Ramanathan, Dhakshin S.; Koloski, Miranda F. (CNS drugs, 2025)
Ketamine and esketamine are increasingly used to manage treatment-resistant depression and have also been shown to reduce symptoms of posttraumatic stress disorder (PTSD). Little is known about how common comorbidities in the veteran population, such as traumatic brain injury (TBI) or obstructive sleep apnea (OSA), may influence ketamine and esketamine treatment outcomes. In this retrospective study, we analyzed clinical outcomes from Veterans Affairs (VA) San Diego Healthcare System's ketamine program to assess the relationship between ketamine or esketamine treatment and changes in depression and PTSD symptoms, while also examining how common medical comorbidities influence treatment outcomes. We specifically examined whether a patient's history of TBI or OSA would affect ketamine or esketamine treatment outcomes. Linear mixed-effects models were used to examine how TBI and OSA history interacted with ketamine/esketamine treatment to change PTSD Checklist for DSM-5 (PCL-5) and Patient Health Questionnaire-9 (PHQ-9) scores. This study included 119 veterans who received eight sessions of ketamine or esketamine treatment at the San Diego VA Medical Center. Using linear effects modeling, we found that repeated ketamine or esketamine sessions were significantly correlated with reductions in both depression (p < 0.005) and PTSD (p < 0.05) symptom scores. However, in veterans with comorbid TBI (n = 38) and severe OSA (n = 9), depression symptoms did not improve over the course of ketamine or esketamine treatment, suggesting this subgroup may require alternative treatments or OSA treatment prior to starting ketamine or esketamine treatment. Ketamine and esketamine treatment did not improve symptoms of depression in veterans with comorbid TBI and severe OSA. Thus, our findings generally support ketamine and esketamine as effective interventions for depression and PTSD, while emphasizing the consideration of comorbidities such as OSA and TBI.